A Tissue Regeneration Approach to Bone and Cartilage Repair - Zreiqat, Hala (Springer, 2016)
Reviewing exhaustively the current state of the art of tissue engineering strategies for regenerating bones and joints through the use of biomaterials, growth factors and stem cells, along with an investigation of the interactions between biomaterials, bone cells, growth factors and added stem cells and how together skeletal tissues can be optimised, this book serves to highlight the importance of biomaterials composition, surface topography, architectural and mechanical properties in providing support for tissue regeneration.